2013
DOI: 10.1371/journal.pone.0055429
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide ENU Mutagenesis in Combination with High Density SNP Analysis and Exome Sequencing Provides Rapid Identification of Novel Mouse Models of Developmental Disease

Abstract: BackgroundMice harbouring gene mutations that cause phenotypic abnormalities during organogenesis are invaluable tools for linking gene function to normal development and human disorders. To generate mouse models harbouring novel alleles that are involved in organogenesis we conducted a phenotype-driven, genome-wide mutagenesis screen in mice using the mutagen N-ethyl-N-nitrosourea (ENU).Methodology/Principal FindingsENU was injected into male C57BL/6 mice and the mutations transmitted through the germ-line. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…The identification of snoopy embryos from a large-scale ENU mutagenesis programme has been reported previously [Caruana et al, 2013]. All mouse procedures were approved by the Royal Children's Hospital Animal Ethics Committee, RCH AEEC No.…”
Section: Micementioning
confidence: 99%
See 2 more Smart Citations
“…The identification of snoopy embryos from a large-scale ENU mutagenesis programme has been reported previously [Caruana et al, 2013]. All mouse procedures were approved by the Royal Children's Hospital Animal Ethics Committee, RCH AEEC No.…”
Section: Micementioning
confidence: 99%
“…Generation of snoopy progeny, DNA extraction from affected snoopy embryos and exome enrichment was performed as described previously [Andrews et al, 2012;Caruana et al, 2013].…”
Section: Exome Enrichment Sequencing Variant Detection and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical mutagenesis combined with exome sequencing has been performed to generate novel mouse models [3,4,5]. The most widely used chemical mutagen is N-ethyl-N-nitrosourea (ENU).…”
Section: Introductionmentioning
confidence: 99%
“…Andrews et al [4] applied exome sequencing to identify a causative mutation of ENU-mutated mice and showed that exome sequencing data alone were sufficient to identify induced mutations. Because 99% of ENU mutations occur in splice sites and exons, the exome sequencing should identify almost all ENU-induced mutations [5]. …”
Section: Introductionmentioning
confidence: 99%